Structure and Composition of forest Vegetation of Kutch (Gujarat State) - Pandya, S. M.; Sidha, V. K. (Indian Forester, 1985)
The paper gives descriptive account of characteristic species, density, cover, distribution and comparison of four forests associations viz; (1) Prosopis juliflora - Salvadors persica, (2) Acacia nilotica - P. cineraria, (3) Euphorbia - Commiphora - Acacia senegal and (4) A. senegal - P. cineraria in the arid regions of the Kutch District of the Gujarat State, India. The Relative Growth/Value Index (RGVI) was maximum in the association No.4, followed by the association nos. 2, 1 and 3. The RGVI is discussed in relation to the distribution of the association.